Evaluating the Validity of a Phenomenon-Based Learning E-Module on Acid-Base Topics Using the Articulate Storyline Application - Abdullah Abdullah; Erviyenni Erviyenni; Berliana Iga Lestari; Tiara Swastika Putri (STAI Hubbulwathan Duri, 2025)
This research aims to assess the validity and effectiveness of an e-module based on Phenomenon-Based Learning (PBL) for teaching acid-base solutions, developed using the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The development method is well-suited for creating educational materials. In this study, the e-module was validated by experts in chemistry content and media design. The validation results indicated that the e-module was highly valid across various aspects, including content, presentation, language, graphics, PBL characteristics, appearance, and software utilization, with validity percentages of 96.00%, 96.66%, 100.00%, 92.00%, 96.36%, and 96.66%, respectively. Additionally, an e-module trial was conducted with feedback from two chemistry teachers and 20 students. The responses were overwhelmingly positive, with effectiveness ratings of 96.66% and 98.76%. Based on these findings, it can be concluded that the e-module developed with the Articulate Storyline application for acid-base solution materials is both valid and effective for use in the learning process.